Armadillo osteoderms altered by digestion and how taphonomy can help taxonomy - Tomassini, Rodrigo Leandro (2023)
Diverse modifications of the original morphological features occur throughout the taphonomic history of osteological remains, which may lead in erroneous interpretations about the formation of an accumulation as well as taxonomic misidentifications. Here, we present a neo-taphonomic study in order to analyze and interpret the modifications generated by digestion on osteoderms of the armadillo Dasypus novemcinctus obtained from scats produced by Puma concolor. Results reveal intense breakage and modifications of the articular and broken edges, dorsal surface, bone tissues, and ornamentation pattern of the osteoderms. This work describes for the first time the modifications caused by digestion in armadillo osteoderms, improving the knowledge of preservation of this type of skeletal element and providing a modern analog that can be used to distinguish archeological and paleontological accumulations formed by predators from those generated by other processes. The recognition that digestion modifies the original ornamentation pattern is particularly significant because ornamentation features are used in nearly all taxonomic and phylogenetic studies of fossil cingulates. We use this new information to re-evaluate osteoderms recovered from carnivore coprolites of the classic middle Miocene La Venta site (Colombia), which formed the basis for recognizing and characterizing the dasypodids species Nanoastegotherium prostatum. We highlight the importance of knowing with certainty the origin and taphonomic history of remains since, in the particular case of cingulates, taxonomic identification also has important biostratigraphic, paleoecological, paleoenvironmental, and paleobiogeographical implications